Aloe vera extract functionalized zinc oxide nanoparticles as nanoantibiotics against multi-drug resistant clinical bacterial isolates - Ali, Khursheed; Dwivedi, Sourabh; Azam, Ameer; Saquib, Quaiser; Al-Said, Mansour S.; Alkhedhairy, Abdulaziz A.; Musarrat, Javed (Journal of colloid and interface science, 2016)
[Display omitted] ZnO nanoparticles (ZnONPs) were synthesised through a simple and efficient biogenic synthesis approach, exploiting the reducing and capping potential of Aloe barbadensis Miller (A. vera) leaf extract (ALE). ALE-capped ZnO nanoparticles (ALE-ZnONPs) were characterized using UV–Vis spectroscopy, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and transmission electron microscopy (TEM) analyses. XRD analysis provided the average size of ZnONPs as 15nm. FTIR spectral analysis suggested the role of phenolic compounds, terpenoids and proteins present in ALE, in nucleation and stability of ZnONPs. Flow cytometry and atomic absorption spectrophotometry (AAS) data analyses revealed the surface binding and internalization of ZnONPs in Gram +ve (Staphylococcus aureus) and Gram −ve (Escherichia coli) cells, respectively. Significant antibacterial activity of ALE-ZnONPs was observed against extended spectrum beta lactamases (ESBL) positive E. coli, Pseudomonas aeruginosa, and methicillin resistant S. aureus (MRSA) clinical isolates exhibiting the MIC and MBC values of 2200, 2400μg/ml and 2300, 2700μg/ml, respectively. Substantial inhibitory effects of ALE-ZnONPs on bacterial growth kinetics, exopolysaccharides and biofilm formation, unequivocally suggested the antibiotic and anti-biofilm potential. Overall, the results elucidated a rapid, environmentally benign, cost-effective, and convenient method for ALE-ZnONPs synthesis, for possible applications as nanoantibiotics or drug carriers.